2020
DOI: 10.4067/s0716-10182020000300244
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico microbiológico y vigilancia epidemiológica de la campilobacteriosis en Chile: Situación actual y desafíos futuros

Abstract: El autor declara no tener conflictos de interés en este tema. Este trabajo fue financiado por Fondo Nacional de Ciencia y Tecnología de Chile (FONDECYT 1200125). Además, el autor agradece el soporte del Núcleo Milenio Biología de la Microbiota Intestinal (NU-GUTmicro).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In countries such as Chile, even though Campylobacter is a notifiable enteric pathogen under active surveillance by public health agencies, routine stool culture–testing for this pathogen is rarely performed. This is partially explained by the high costs associated with the culture of this bacterium, including the need for special selective media and specific temperature and microaerophilic growth conditions [ 50 ]. As a consequence, there is limited genomic, clinical and epidemiological data available from the region, leaving an important knowledge gap in our understanding of the global population structure, virulence potential, and antimicrobial resistance profiles of clinical Campylobacter strains [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In countries such as Chile, even though Campylobacter is a notifiable enteric pathogen under active surveillance by public health agencies, routine stool culture–testing for this pathogen is rarely performed. This is partially explained by the high costs associated with the culture of this bacterium, including the need for special selective media and specific temperature and microaerophilic growth conditions [ 50 ]. As a consequence, there is limited genomic, clinical and epidemiological data available from the region, leaving an important knowledge gap in our understanding of the global population structure, virulence potential, and antimicrobial resistance profiles of clinical Campylobacter strains [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stool culture is the diagnostic standard for Campylobacter spp. ; however, the high costs and complexity of this method have prevented its routine implementation in many resource-limited countries, although the pathogen seems to be of emerging epidemiological relevance in these regions [ 5 , 6 ]. The epidemiology and spectrum of campylobacteriosis in South America are uncertain [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies in Chile demonstrated prevalence rates from 0.4%, using microscopy, to 18%, using culture [ 8 ]. A clinical study showed an increase in the detection of campylobacteriosis from 0.4% to 6.1% after the implementation of culture methods within routine stool workflow [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to ciprofloxacin (30–60%), tetracycline (2–24%) and erythromycin (2–6%) has been reported in clinical isolates of C. jejuni in Chile (Collado 2020). However, the origin of this resistance is unknown, although it has been suggested that it may originate in part from the Chilean poultry industry, due to the high rates of resistance previously found in Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%